Validity and reliability testing of the Toddler and Infant (TANDI) Health Related Quality of Life instrument for very young children - Janine Verstraete; Lebogang Ramma; Jennifer Jelsma (SpringerOpen, 2020)
Abstract Background Despite the high burden of disease in younger children there are few tools specifically designed to estimate Health Related Quality of Life (HRQoL) in children younger than 3 years of age. A previous paper described the process of identifying a pool of items which might be suitable for measuring HRQoL of children aged 0-3 years. The current paper describes how the items were pruned and the final draft of the measure, Toddler and Infant (TANDI) Health Related Quality of Life, was tested for validity and reliability. Methods A sample of 187 caregivers of children 1-36 months of age were recruited which included children who were either acutely ill (AI), chronically ill (CI) or from the general school going population (GP). The TANDI, an experimental version of the EQ-5D-Y proxy, included six dimensions with three levels of report and general health measured on a Visual Analogue Scale (VAS) from 0 to 100. The content validity had been established during the development of the instrument. The TANDI, Ages and Stages Questionnaire (ASQ), Faces, Leg, Activity, Cry, Consolabilty (FLACC) or Neonatal Infant Pain Scale (NIPS) and a self-designed dietary information questionnaire were administered at baseline. The TANDI was administered 1 week later in GP children to establish test-retest reliability. The distribution of dimension scores, Cronbach's alpha, rotated varimax factor analysis, Spearman's Rho Correlation, the intraclass correlation coefficient, Pearson's correlation, analysis of variance and regression analysis were used to explore the reliability, and validity of the TANDI. Results Concurrent validity of the different dimensions was tested between the TANDI and other instruments. The Spearman's Rho coefficients were significant and moderate to strong for dimensions of activity and participation and significant and weak for items of body functions. Known groups were compared and children with acute illness had the lowest ranked VAS (median 60, range 0-100), indicating worse HRQoL. The six dimensions of the TANDI were tested for internal consistency and reliability and the Cronbach's α as 0.83. Test-retest results showed no variance for dimension scores of movement and play, and high agreement for pain (83%), relationships (87%), communication (83%) and eating (74%). The scores were highly correlated for the VAS (ICC = 0.76; p < 0.001). Conclusion The TANDI was found to be valid and reliable for use with children aged 1-36 months in South Africa. It is recommended that the TANDI be included in future research to further investigate HRQoL and the impact of interventions in this vulnerable age group. It is further recommended that future testing be done to assess the feasibility, clinical utility, and cross-cultural validity of the measure and to include international input in further development.